Analisis Pengaruh Lingkungan terhadap Modal Intelektual Organisasi - Engkos Achmad Kuncoro (Bina Nusantara University, 2007)
The research purpose was to describe and analyze how far the influence of external and organization environment as independent variable to individual intellectual competence transformation process to become organization intellectual capital, as dependent variable. The research method used in this research is the survey method with quantitative approach. Research result show that exogen variable of External Environment LE) has influence of 0.565 or 56.5%, and 0,661 or 66,1 % of variable Organization Climate (IKO) to Intellectual Competence (KII) as intervening variable. Meanwhile Intervening KII variable has influence of 0.609 or 60.9% on Intellectual Capital (INO) as endogen variable.